Born to Write: Discovery and Construction of Self in the Identity Stories of Poets and Writers - Ben-Shir, Deborah (Qualitative Sociology Review, 2008)
The explorative study hereby presented is based on in-depth interviews with 16 renowned Israeli writers of prose and poetry. The aim of the study is to examine the identity-stories of these masters of the written word. By the term "identity-story", we relate to the self-reflective or "arspoetic" sides of the life stories our interviewees presented, the hows, whens and whys which had brought them to realize their identities as their cultures’ authorized authors or poets. Thematic analysis of these stories, conducted in the spirit of the Schutzian Phenomenological-Interpretive approach, reveals an interesting interplay of two seemingly contradictory core meta-themes - identity-creation and identity-discovery. The present paper is focused on the identity-discovery meta-theme. Unlike the identitycreation meta-theme, which illustrates active, deliberate and conscious processes of identity construction within the social world, the identitydiscovery meta-theme is based on narratives that detect the belief in the feasibility of a transcendental revelation of a given identity, whose roots lies beyond the ties of time and place.